PENERAPAN TERAPI SEFT TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Jamaludin Jamaludin; Febyana Galuh Astanti; Renny Wulan Apriliyasari (Jurnal Profesi Keperawatan, 2026)
Background: Hypertension is a condition where a person experiences an increase in blood pressure that exceeds normal limits. A person is considered to have hypertension if their blood pressure is more than 140/90 mmHg. An increase in blood pressure occurs when there is an increase in systole and diastole, which varies depending on the individual affected. Spiritual emotional freedom technique (SEFT) therapy is a therapy in the form of a combination of energy systems (energy medicine) and spiritual therapy combined with tapping at a predetermined point on several parts of the body which is almost the same as acupuncture and acupressure techniques by stimulating several key points along the 12 energy pathways (energy meridians) of the body. Objective: To describe the implementation of SEFT therapy in lowering blood pressure in hypertensive patients. Methods: The case study in this scientific paper uses a pre experimental design method using the form of a one group pre test - post test design. Results: after being given SEFT therapy for 3 consecutive days, it was found that the majority of hypertensive patients were female with a percentage of 66.67%, with age characteristics of 46-55 years (early elderly period) with a percentage of 60%, and work characteristics as housewives with a percentage of 40%. The average blood pressure value of 15 pre-test respondents was 170 mmHg for systolic blood pressure and 94 mmHg for diastolic blood pressure. The average post test blood pressure value of 15 respondents was 152 mmHg for systolic blood pressure and 87 mmHg for diastolic blood pressure. The difference between the average pre-test and post-test blood pressure values of 15 respondents is 18 mmHg for systolic blood pressure and 7 mmHg for diastolic blood pressure. These results indicate that there is a decrease in blood pressure values in hypertensive patients in Growong Village after SEFT therapy.